The Aynho Cartulary and its documentary culture study, text, and translation - Allen, Richard Blair; Pohl, Benjamin 1985- (The Boydell Press, 2025)
"A major contribution to scholarship on medieval roll cartularies, shedding light both on the Aynho Cartulary itself and on the wider social, political, and economic culture that produced it. Despite being one of the earliest and best preserved of its type in Britain and Ireland, the thirteenth-century roll cartulary of the wayfarer hospital of SS James and John in Aynho, Northamptonshire, has received almost no scholarly attention to date. This book offers the first full study of this fascinating document, which is now conserved in the archives of Magdalen College, Oxford, together with a critical edition and translation. Combining extensive historical and prosopographical research with a focussed examination of the cartulary's contents and a forensic scribal and material analysis, it takes an holistic approach to - and aims to provide a model for - the study of these types of artefacts and the documentary cultures and societies that produced them. Uniting three areas of scholarship which are rarely brought into dialogue (the study of medieval cartularies, rolls, and hospitals), the volume's innovative approach demonstrates how such an examination of the Aynho Cartulary can shed light on the social, political, economic, spiritual, and scribal networks within which this relatively obscure but well-connected hospital was situated. Written with experienced researchers and students in mind, this book is designed to be a go-to resource for both"--
Keywords: Geschichte; Kopialbuch; Aynho; Aynho (England) / History / Sources; Quelle